Impact of Board Characteristics, Company Performance and Ownership Structures on Executive Management Compensation - Hassan, Mohammed (The Arab Journal of Administration, 2021)
Factors affecting executive management compensation cannot be limited, but this study seeks to determine the impact of the characteristics of the board of directors, company performance and ownership structure on this compensation. Through testing the effect of these variables on the compensation of the executive management, on a sample of companies listed on the Saudi Stock Exchange. To achieve this goal, the study used correlation analysis to test the validity of the study hypotheses. The study used regression analysis to estimate the study model. The study found that there is very little correlation between executive compensation and the number of independent members and foreign members of the board. It also concluded that ownership of major shareholders is the only variable that has the ability to explain the variation in executive compensation. The study recommended reducing conflicts of interest between owners and management by linking management compensation to the company’s performance.